Psychological Problems Encountered by EFL Students in Speaking Class at Universitas Islam Riau - Muhammad Ilyas; Miranti Eka Putri; Isnania Nurani (J-SHMIC : Journal of English for Academic, 2021)
The target of the study is to give perspectives to the English teachers or lecturers about the psychological problems encountered by students. It also will be used as the basic information for teachers or lecturers to find the best way in teaching and learning English especially in English speaking skill classroom. This study was a qualitative design that would be analyzed in form of description and were collected from the second semester students of English Study Program of Universitas Islam Riau. The questionnaires were distributed to 15 students while five out of them were interviewed to assure their responses towards 18 statements in the questionnaire. Moreover, the questionnaire comprised statements that based on the psychological problem that consist of low of self-confidence, anxiety, and low of self-esteem. It was found that the students faced the psychological problem. The problems that prominently encountered by the students was low of self-esteem, which stated that they were unable to speak in English as well as most of their friends. Then, they felt they had not much to be proud during the class due to several problems. Most of the students tend to feel they were failure, because they have not improved their speaking skills yet, due to several problems which encounter them at the same time.